Study on the improvement of the open TBM system and supporting equipment based on the Gaojiapu Coal Mine - Liu, Yexian; Ren, Dengjun; Zhou, Changkuan; Qiu, Huafu; Ding, Ziwei; Liang, Chao (Frontiers in Earth Science, 2023)
In order to cope with the multi-dimensional mine disasters in deep mines, enhance the adaptability of open tunnel boring machine (TBM) to the actual mine working face environment and improve the excavation speed of open TBM, based on the excavation project of Gaojiapu Coal Mine in Zhengtong Coal Industry, Shaanxi Province, this paper comprehensively considers the difficulties encountered by TBM in the excavation process, and improves the open TBM system and its supporting equipment. The research shows that removing the redundant system and supporting equipment of the open TBM can effectively solve the difficulties of TBM entering the mine, loading and unloading, turning and so on; Optimizing the open TBM shield, shortening the main beam and setting the support platform and jumbolter system on the main beam can deal with the problem that the TBM support is not timely and easy to jam; Opening circular holes and installing slag cleaning guide plates on the main beam of the open TBM can timely clean up the waste slag on the main beam and protect the main beam from deformation; Installing a slag cleaning bucket wheel machine between the main beam of the open TBM and the trailer can reduce the accumulation of waste slag on the road ahead; Compared with the ordinary excavation construction technology, the monthly average footage level of the open TBM after technical improvement is 300.88 m, which is 3.8 times that of the rock roadway general excavation and 1.6 times that of the rock roadway comprehensive excavation.